Simple Perylene Diimide Cyclohexane Derivative With Combined CPL and TPA Properties - Reine, Pablo; Ortuño, Ana M.; Mariz, Inês F. A.; Ribagorda, Maria; Cuerva, Juan M.; Campaña, Araceli G.; Maçôas, Emerlinda; Miguel, Delia (Frontiers in Chemistry, 2020)
In this work we describe the linear and non-linear (chiro)optical properties of an enantiopure bis-perylenediimide (PDI) cyclohexane derivative. This compound exhibits upconversion based on a two-photon absorption (TPA) process with a cross-section value of 70 GM together with emission of circularly polarized luminescence (CPL), showing a glum in the range of 10−3. This simple structure represents one of the scarce examples of purely organic compounds combining both TPA and CPL responses, together with large values of molar absorptivity and fluorescence quantum yield with emission in the 500–600 nm. Self-assembly induced by introduction of a poor solvent allows for a spectacular shift of the emission into the near-infrared (NIR, 650–750 nm) by formation of well-defined rotationally displaced dimers. Therefore, we are here presenting a versatile platform whose optical properties can be simply tuned by self-assembly or by functionalization of the electron-deficient aromatic core of PDIs.